A sodium ion battery positive electrode slurry and preparation method thereof, positive electrode sheet and sodium ion battery

By forming a hydrophobic layer on the surface of the positive electrode sheet of the sodium ion battery and reducing the residual alkali on the surface, the poor circulation performance problem caused by the high alkalinity of the layered transition metal oxides of sodium-containing layered transition metal oxides is solved, and a higher baking effect and battery performance are achieved.

CN115799469BActive Publication Date: 2025-03-04CHUGU TECH (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211536810.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-03-04
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The sodium-containing layered transition metal oxides have poor circulation performance of sodium ion batteries due to their high alkalinity.

Method used

By optimizing the slurry formula and process, adding hydrophobic materials to form a hydrophobic layer on the surface of the positive electrode sheet, and adding weak acidic substances to reduce the side effects of residual alkali on the surface of the layered transition metal oxide containing sodium.

Benefits of technology

It improves the baking effect, battery production efficiency and circulation performance, and extends the circulation life of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799469B_ABST
    Figure CN115799469B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode slurry and a preparation method thereof, a positive electrode sheet and a sodium ion battery, wherein the preparation method of the sodium ion battery positive electrode slurry comprises the following steps: (1) mixing N-methyl pyrrolidone with cholesterol dodecyl carbonate and a weakly acidic substance to obtain a solution; (2) mixing the obtained solution with a binder to obtain a glue solution; (3) mixing the obtained glue solution with a conductive agent to obtain a conductive glue; (4) mixing the obtained conductive glue with a sodium-containing layered transition metal oxide to obtain a sodium ion battery positive electrode slurry. The present invention optimizes the slurry formula and process, adds a hydrophobic material, forms a hydrophobic layer on the surface of the positive electrode sheet, and simultaneously adds a weakly acidic substance to reduce the side effects of residual alkali on the surface of the sodium-containing layered transition metal oxide, thereby improving the baking effect and the production efficiency and recycling performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode slurry and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have been widely studied in recent years. Due to their low cost, good low-temperature performance, and long service life, and the fact that sodium resources are far more abundant and more widely distributed than lithium, sodium-ion batteries have become a new generation of electrochemical systems with great potential to replace lithium-ion batteries.

[0003] Cathode active materials are key factors affecting the performance of sodium-ion batteries. Among the various cathode active materials that have been widely studied, such as oxides, fluorides, sulfides, phosphates, pyrophosphates, metal-organic frameworks / metal hexcyanides, and organic compounds, transition metal oxide cathode active materials with layered structures have received extensive attention due to their high theoretical capacity, high density, and ease of material preparation. They have become a highly potential cathode active material for sodium-ion batteries and have been demonstrated in 100kW·h sodium-ion battery energy storage power stations. However, the sodium-containing layered transition metal oxides still have the problem of high alkalinity and poor sodium-ion battery cycle performance.

[0004] Therefore, in view of the above-mentioned defects of the current sodium-containing layered transition metal oxides, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0005] One of the purposes of the present invention is to provide a positive electrode slurry for a sodium ion battery, by optimizing the slurry formula and process, adding a hydrophobic material, forming a hydrophobic layer on the surface of the positive electrode sheet, and adding a weak acidic substance to reduce the side effects of residual alkali on the surface of the sodium-containing layered transition metal oxide, thereby improving the baking effect and the production efficiency and cycle performance of the battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a positive electrode slurry for a sodium ion battery comprises the following steps:

[0008] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weakly acidic substance to obtain a solution;

[0009] (2) mixing the solution obtained in step (1) with a binder to obtain a glue solution;

[0010] (3) mixing the adhesive obtained in step (2) with a conductive agent to obtain a conductive adhesive;

[0011] (4) The conductive glue obtained in step (3) is mixed with a sodium-containing layered transition metal oxide to obtain a positive electrode slurry for a sodium ion battery.

[0012] According to some embodiments of the present invention, in step (1), the weak acidic substance is at least one of oxalic acid, acetic acid, and carbonic acid, preferably oxalic acid, and the mass ratio of the N-methylpyrrolidone to the cholesterol dodecyl carbonate and the weak acidic substance is (88-92):(3-7):(3-7), preferably 90:5:5.

[0013] According to some embodiments of the present invention, in step (2), the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylate and aqueous polyurethane, and the mass ratio of the solution to the binder is (93-97):(3-7), preferably 95:5.

[0014] According to some embodiments of the present invention, in step (3), the conductive agent includes at least one of carbon nanotubes, conductive carbon black, conductive graphite, carbon fiber, and graphene, and the mass ratio of the glue to the conductive agent is (94-97):(3-6), preferably 96:4.

[0015] According to some embodiments of the present invention, in step (4), the chemical formula of the sodium-containing layered transition metal oxide is NaMO 2 , wherein M is a transition metal cation, and the transition metal cation is at least one of Mn, Ni, Cr, Fe, Ti, and V. Preferably, the chemical formula of the sodium-containing layered transition metal oxide used in the present application is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 .

[0016] According to some embodiments of the present invention, the mass ratio of the conductive adhesive to the sodium-containing layered transition metal oxide is (1-3): (1-3), preferably 1:1.

[0017] A second object of the present invention is to provide a sodium ion battery positive electrode slurry prepared by the above method.

[0018] A third object of the present invention is to provide a positive electrode sheet, comprising a positive electrode collector and the above-mentioned sodium ion battery positive electrode slurry coated on the surface of the positive electrode collector.

[0019] According to some embodiments of the present invention, the coating thickness is 150-300 μm, preferably 200-250 μm.

[0020] A fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.

[0021] The beneficial effects of the present invention are as follows: the sodium ion battery positive electrode slurry provided in the present application optimizes the slurry formula and process, adds hydrophobic materials, forms a hydrophobic layer on the surface of the positive electrode sheet, and adds weakly acidic substances at the same time, thereby reducing the side effects of residual alkali on the surface of the sodium-containing layered transition metal oxide, improving the baking effect and the production efficiency and cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process diagram for preparing a positive electrode slurry for a sodium ion battery according to an embodiment of the present application. DETAILED DESCRIPTION

[0023] According to a first aspect of the present invention, a positive electrode slurry for a sodium ion battery is provided. By optimizing the slurry formula and process, a hydrophobic material is added to form a hydrophobic layer on the surface of the positive electrode sheet, and a weak acidic substance is added at the same time to reduce the side effects of residual alkali on the surface of the sodium-containing layered transition metal oxide, thereby improving the baking effect and the production efficiency and cycle performance of the battery.

[0024] In order to achieve the above object, the present invention adopts the following technical solutions:

[0025] A method for preparing a positive electrode slurry for a sodium ion battery comprises the following steps:

[0026] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weakly acidic substance to obtain a solution;

[0027] (2) mixing the solution obtained in step (1) with a binder to obtain a glue solution;

[0028] (3) mixing the adhesive obtained in step (2) with a conductive agent to obtain a conductive adhesive;

[0029] (4) The conductive glue obtained in step (3) is mixed with a sodium-containing layered transition metal oxide to obtain a positive electrode slurry for a sodium ion battery.

[0030] According to some embodiments of the present invention, in step (1), the weak acidic substance is at least one of oxalic acid, acetic acid, and carbonic acid, preferably oxalic acid, and the mass ratio of the N-methylpyrrolidone to the cholesterol dodecyl carbonate and the weak acidic substance is (88-92):(3-7):(3-7), preferably 90:5:5. At this time, the cholesterol dodecyl carbonate and the weak acidic substance can be well dispersed in the N-methylpyrrolidone to make the formed solution more uniform, and the role of the weak acidic substance is to reduce the surface residual alkali of the sodium-containing layered transition metal oxide to avoid the formation of jelly during stirring.

[0031] According to some embodiments of the present invention, in step (2), the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylate and waterborne polyurethane, and the mass ratio of the solution to the binder is (93-97): (3-7), preferably 95: 5. Controlling the mass ratio of the two within this range can ensure that the viscosity of the slurry is moderate. If the mass ratio of the two is too large, the viscosity is too large, and if the mass ratio of the two is too small, the viscosity is too small, which is not conducive to the subsequent steps.

[0032] According to some embodiments of the present invention, in step (3), the conductive agent includes at least one of carbon nanotubes, conductive carbon black, conductive graphite, carbon fiber, and graphene, and the mass ratio of the glue solution to the conductive agent is (94-97): (3-6), preferably 96: 4. At this time, cholesterol dodecyl carbonate and the colloidal conductive agent together form a gel-linked structure and a membrane structure of the sodium-containing sodium ion battery positive electrode slurry.

[0033] According to some embodiments of the present invention, in step (4), the chemical formula of the sodium-containing layered transition metal oxide is NaMO 2 , wherein M is a transition metal cation, and the transition metal cation is at least one of Mn, Ni, Cr, Fe, Ti, and V. The chemical formula of the sodium-containing layered transition metal oxide used in the present application is NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 .

[0034] According to some embodiments of the present invention, the mass ratio of the conductive adhesive to the sodium-containing layered transition metal oxide is (1-3): (1-3), preferably 1:1.

[0035] According to a second aspect of the present invention, a sodium ion battery positive electrode slurry prepared by the above method is provided.

[0036] According to a third aspect of the present invention, a positive electrode sheet is provided, comprising a positive electrode current collector and the above-mentioned positive electrode slurry for sodium ion battery coated on the surface of the positive electrode current collector. The positive electrode current collector may be a metal foil, preferably an aluminum foil.

[0037] According to some embodiments of the present invention, the coating thickness is 150-300 μm, preferably 200-250 μm. When the coating thickness is controlled within the above range, the drying effect of the positive electrode sheet and the rate performance of the sodium ion battery are best.

[0038] According to a fourth aspect of the present invention, a sodium ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet described above.

[0039] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material used in the negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, etc. The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector may be copper foil, PET copper foil or aluminum foil.

[0040] The separator can be selected from various separators used in lithium-ion batteries known to those skilled in the art, such as polypropylene microporous membrane, polyethylene felt, glass fiber felt or ultrafine glass fiber paper.

[0041] The lithium-ion battery also includes an electrolyte, which can be any conventional electrolyte, such as a non-aqueous electrolyte. The non-aqueous electrolyte is a solution of an electrolyte lithium salt in a non-aqueous solvent, and conventional non-aqueous electrolytes known to those skilled in the art can be used. For example, the electrolyte can be selected from lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ) lithium hexafluoroarsenate (LiAsF 6 ) and lithium hexafluorosilicate (LiSiF 6 ). The non-aqueous solvent may be selected from a mixed solution of a chain acid ester and a cyclic acid ester, wherein the chain acid ester may be at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC) and dipropyl carbonate (DPC). The cyclic acid ester may be at least one of ethylene carbonate (EC), propylene carbonate (PC) and vinylene carbonate (VC).

[0042] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Example 1

[0044] A method for preparing a positive electrode slurry for a sodium ion battery comprises the following steps:

[0045] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance in a mass ratio of 90:5:5 to obtain a solution;

[0046] (2) mixing the solution obtained in step (1) with a binder in a mass ratio of 95:5 to obtain a glue solution;

[0047] (3) mixing the adhesive obtained in step (2) with a conductive agent in a mass ratio of 96:4 to obtain a conductive adhesive;

[0048] (4) The conductive glue obtained in step (3) is mixed with the sodium-containing layered transition metal oxide in a mass ratio of 1:1 to obtain a positive electrode slurry for a sodium ion battery.

[0049] The positive electrode slurry of the sodium ion battery prepared by the above method is coated on the surface of the positive electrode collector to make a positive electrode sheet, and then the positive electrode sheet is used to make a sodium ion battery.

[0050] Example 2

[0051] Different from Example 1, the method for preparing the positive electrode slurry for a sodium ion battery in this embodiment comprises the following steps:

[0052] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance in a mass ratio of 92:4:4 to obtain a solution;

[0053] (2) mixing the solution obtained in step (1) with a binder in a mass ratio of 94:6 to obtain a glue solution;

[0054] (3) mixing the adhesive obtained in step (2) with a conductive agent in a mass ratio of 95:5 to obtain a conductive adhesive;

[0055] (4) The conductive glue obtained in step (3) is mixed with the sodium-containing layered transition metal oxide in a mass ratio of 1.2:1 to obtain a positive electrode slurry for a sodium ion battery.

[0056] The positive electrode slurry of the sodium ion battery prepared by the above method is coated on the surface of the positive electrode collector to make a positive electrode sheet, and then the positive electrode sheet is used to make a sodium ion battery.

[0057] Example 3

[0058] Different from Example 1, the method for preparing the positive electrode slurry for a sodium ion battery in this embodiment comprises the following steps:

[0059] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance in a mass ratio of 88:6:6 to obtain a solution;

[0060] (2) mixing the solution obtained in step (1) with a binder in a mass ratio of 96:4 to obtain a glue solution;

[0061] (3) mixing the adhesive obtained in step (2) with a conductive agent in a mass ratio of 94:6 to obtain a conductive adhesive;

[0062] (4) The conductive glue obtained in step (3) is mixed with the sodium-containing layered transition metal oxide in a mass ratio of 2:1.8 to obtain a positive electrode slurry for a sodium ion battery.

[0063] The positive electrode slurry of the sodium ion battery prepared by the above method is coated on the surface of the positive electrode collector to make a positive electrode sheet, and then the positive electrode sheet is used to make a sodium ion battery.

[0064] Example 4

[0065] Different from Example 1, the method for preparing the positive electrode slurry for a sodium ion battery in this embodiment comprises the following steps:

[0066] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance in a mass ratio of 90:5:5 to obtain a solution;

[0067] (2) mixing the solution obtained in step (1) with a binder in a mass ratio of 94:6 to obtain a glue solution;

[0068] (3) mixing the adhesive obtained in step (2) with a conductive agent in a mass ratio of 95:5 to obtain a conductive adhesive;

[0069] (4) The conductive glue obtained in step (3) is mixed with the sodium-containing layered transition metal oxide in a mass ratio of 1:1.2 to obtain a positive electrode slurry for a sodium ion battery.

[0070] The positive electrode slurry of the sodium ion battery prepared by the above method is coated on the surface of the positive electrode collector to make a positive electrode sheet, and then the positive electrode sheet is used to make a sodium ion battery.

[0071] Example 5

[0072] Different from Example 1, the method for preparing the positive electrode slurry for a sodium ion battery in this embodiment comprises the following steps:

[0073] (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance in a mass ratio of 92:4:4 to obtain a solution;

[0074] (2) mixing the solution obtained in step (1) with a binder in a mass ratio of 93:7 to obtain a glue solution;

[0075] (3) mixing the adhesive obtained in step (2) with a conductive agent in a mass ratio of 97:3 to obtain a conductive adhesive;

[0076] (4) The conductive glue obtained in step (3) is mixed with the sodium-containing layered transition metal oxide in a mass ratio of 3:2.8 to obtain a positive electrode slurry for a sodium ion battery.

[0077] The positive electrode slurry of the sodium ion battery prepared by the above method is coated on the surface of the positive electrode collector to make a positive electrode sheet, and then the positive electrode sheet is used to make a sodium ion battery.

[0078] Comparative Example 1

[0079] A sodium ion battery positive electrode slurry containing sodium layered transition metal oxide is prepared using a conventional scheme, and the sodium ion battery positive electrode slurry is coated on the surface of a positive electrode collector to make a positive electrode sheet, and the positive electrode sheet is used to make a sodium ion battery.

[0080] The state of the slurry after standing and the water content and the number of cycles in the process of making sodium ion batteries of Examples 1-5 and Comparative Example 1 are as follows:

[0081]

[0082]

[0083] It can be seen from the test results in the table that the positive electrode slurry of the sodium ion battery prepared in the embodiment of the present application does not appear jelly-like after standing and has good fluidity, while the positive electrode slurry of the sodium ion battery prepared by the conventional method appears jelly-like after standing and has poor fluidity; in the process of making the sodium ion battery, the water content of the positive electrode sheet coated with the positive electrode slurry of the sodium ion battery of the present application during coating, lamination and baking is relatively small compared with the positive electrode sheet coated with the positive electrode slurry of the sodium ion battery prepared by the conventional method, and when the water content of the positive electrode sheet is baked to 200ppm, the baking time required for the present application is much less than the time required for the positive electrode sheet coated with the positive electrode slurry of the sodium ion battery prepared by the conventional method, and even only requires a quarter of the time required; when the sodium ion battery is charged and discharged at 1C / 1C, and the battery capacity retention rate after the cycle is 80% of the original, the number of cycles of the present application is much greater than the number of cycles of the sodium ion battery made of the positive electrode sheet obtained by coating the positive electrode slurry of the sodium ion battery prepared by the conventional method.

[0084] It can be seen from the test results of Examples 1-5 that when the ratio of the raw materials in the technical scheme is different, it will also affect the test results. In Example 1, N-methylpyrrolidone, cholesterol dodecyl carbonate and a weakly acidic substance are mixed in a mass ratio of 90:5:5 to form a solution, and the solution is mixed with a binder in a mass ratio of 95:5 to form a glue solution, and then mixed with a conductive agent in a mass ratio of 96:4 to form a conductive glue, and finally mixed with a sodium-containing layered transition metal oxide in a mass ratio of 1:1 to obtain a sodium ion battery positive electrode slurry. Compared with other embodiments, in the process of making lithium ion batteries, the water content of the positive electrode sheet is the lowest, the time required for baking to a water content of 200ppm is also the shortest, and the cycle life of the sodium ion battery is also the longest. Therefore, the raw material ratio of the sodium ion battery positive electrode slurry in Example 1 is the best ratio of this application. Furthermore, the test results of Example 1 and Comparative Example 1 show that compared with the positive electrode sheet prepared by coating the positive electrode slurry of the sodium ion battery of the present application and the positive electrode sheet directly coated with the positive electrode slurry of the sodium ion battery prepared by the conventional method, the increase in water content of the present application during coating, lamination and baking is relatively low. When the positive electrode sheet is baked to a water content of 200ppm, the baking time of the present application is only one-fourth of the positive electrode sheet of the sodium ion battery positive electrode slurry prepared by the conventional method, and the sodium ion battery is charged and discharged at 1C / 1C, and the battery capacity retention rate after the cycle is 80% of the original, the number of cycles of the present application is twice that of the positive electrode sheet, that is, the sodium ion battery prepared by the present application has a longer cycle life.

[0085] In summary, this application optimizes the slurry formula and process, adds hydrophobic materials, forms a hydrophobic layer on the surface of the positive electrode, and adds weakly acidic substances to reduce the side effects of residual alkali on the surface of the sodium-containing layered transition metal oxide, thereby improving the baking effect and the production efficiency and recycling performance of the battery.

[0086] Therefore, the present application solves the problem that sodium-containing layered transition metal oxides have poor cycle performance in sodium ion batteries due to their high alkalinity.

[0087] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing a positive electrode slurry for a sodium ion battery, characterized in that: The following steps are involved: (1) mixing N-methylpyrrolidone, cholesterol dodecyl carbonate and a weak acidic substance to obtain a solution; (2) mixing the solution obtained in step (1) with a binder to obtain a glue solution; (3) mixing the adhesive obtained in step (2) with a conductive agent to obtain a conductive adhesive; (4) mixing the conductive glue obtained in step (3) with a sodium-containing layered transition metal oxide to obtain a positive electrode slurry for a sodium ion battery; The weakly acidic substance is at least one of oxalic acid, acetic acid, and carbonic acid; the chemical formula of the sodium-containing layered transition metal oxide is NaMO2, wherein M is a transition metal cation, and the transition metal cation is at least one of Mn, Ni, Cr, Fe, Ti, and V elements.

2. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: In step (1), the mass ratio of the N-methylpyrrolidone to the cholesterol dodecyl carbonate and the weakly acidic substance is (88-92):(3-7):(3-7).

3. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: In step (2), the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylate and water-based polyurethane, and the mass ratio of the solution to the binder is (93-97): (3-7).

4. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: In step (3), the conductive agent includes at least one of carbon nanotubes, conductive carbon black, conductive graphite, carbon fiber, and graphene, and the mass ratio of the glue to the conductive agent is (94-97): (3-6).

5. The method for preparing a positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The mass ratio of the conductive adhesive to the sodium-containing layered transition metal oxide is (1-3): (1-3).

6. A positive electrode slurry for a sodium ion battery, characterized in that: The sodium ion battery positive electrode slurry is prepared by the preparation method of the sodium ion battery positive electrode slurry according to any one of claims 1 to 5.

7. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode slurry coated on the surface of the positive electrode current collector, wherein the positive electrode slurry is the positive electrode slurry for a sodium ion battery according to claim 6.

8. A positive electrode sheet according to claim 7, characterized in that: The coating thickness is 150-300 μm.

9. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet described in any one of claims 7-8.

Citation Information

Patent Citations

  • Sodium ion total battery and preparation method thereof

    CN114792788A

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN115133003A